The role of ultrasound-guided transcutaneous tru-cut biopsy in diagnosing untreated and recurrent laryngo-hypopharyngeal masses. Issue 1 (January 2016) - De Fiori, Elvio; Conte, Giorgio; Ansarin, Mohssen; De Benedetto, Luigi; Bonello, Luke; Alterio, Daniela; Maffini, Fausto; Bellomi, Massimo; Preda, Lorenzo
Abstract: Objective: To evaluate the diagnostic performance of Ultrasound-guided Transcutaneous Tru-Cut biopsy (USGTCB) of laryngo-hypopharyngeal masses suspicious for malignancy. Furthermore we investigated whether USGTCB is accurate for both untreated masses and suspected recurrences. Materials and methods: From August 2004 to July 2014 we prospectively enrolled 66 patients for a total of 68 USGTCBs: 38 USGTCB were performed for a suspicious untreated mass and in 30 for a suspected recurrence. We calculated the sensitivity, specificity, positive predictive value and negative predictive value for all procedures and separately for untreated masses and suspected recurrences. Results: USGTCB diagnosed 57 malignancies (51 squamous cell carcinomas, 6 other tumors) and 11 benign lesions. There were no false positives reported, whereas five false negatives were observed: two in patients with an untreated mass, three in patients with a suspected recurrence. Overall, the sensitivity of the technique was 91.9% (95% confidence interval [CI]: 82.2–97.3%); the specificity was 100% (95% CI: 54.1–100%); positive and negative predictive values were 100% (95% CI: 93.7–100%) and 54.5% (95% CI: 23.5–83.1%) respectively, with similar performances in untreated masses and suspected recurrences of SCC. Conclusion: USGTCB is an effective procedure for the histological diagnosis of laryngo-hypopharyngeal masses suspicious for malignancy in patients showing contraindications to biopsy via microlaryngoscopy under general, with similar performances for untreated masses and suspected recurrences.